2012
DOI: 10.1039/c2mb25282a
|View full text |Cite
|
Sign up to set email alerts
|

The Botrytis cinerea type III polyketide synthase shows unprecedented high catalytic efficiency toward long chain acyl-CoAs

Abstract: BPKS from Botrytis cinerea is a novel type III polyketide synthase that accepts C(4)-C(18) aliphatic acyl-CoAs and benzoyl-CoA as the starters to form pyrones, resorcylic acids and resorcinols through sequential condensation with malonyl-CoA. The catalytic efficiency (k(cat)/K(m)) of BPKS was 2.8 × 10(5) s(-1) M(-1) for palmitoyl-CoA, the highest ever reported. Substrate docking analyses addressed the unique features of BPKS such as its high activity and high specificity toward long chain acyl-CoAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
(29 reference statements)
3
20
0
Order By: Relevance
“…In vitro characterization of a recombinant ORAS protein showed that this enzyme can accommodate C4 to C20 fatty acyl-CoA starter units, but it exhibits a clear preference for longer chains to produce tetra and pentaketide resorcylic acids (Funa et al, 2007). Similar results were obtained with recombinant Aspergillus niger AnPKS and An-CsyA (Li et al, 2011;Kirimura et al, 2016), Botrytis cinerea BPKS (Jeya et al, 2012), Sporotrichum laxum Sl-PKS2 (Sun et al, 2016), Sordaria macrospora SmPKS and Chaetomium thermophilum CtPKS (Ramakrishnan et al, 2018), and Fusarium incarnatum FiPKS (Manoharan et al, 2019). However, fungal type III PKSs expressed in a fungal host yield compounds that are different from the recombinant proteins.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In vitro characterization of a recombinant ORAS protein showed that this enzyme can accommodate C4 to C20 fatty acyl-CoA starter units, but it exhibits a clear preference for longer chains to produce tetra and pentaketide resorcylic acids (Funa et al, 2007). Similar results were obtained with recombinant Aspergillus niger AnPKS and An-CsyA (Li et al, 2011;Kirimura et al, 2016), Botrytis cinerea BPKS (Jeya et al, 2012), Sporotrichum laxum Sl-PKS2 (Sun et al, 2016), Sordaria macrospora SmPKS and Chaetomium thermophilum CtPKS (Ramakrishnan et al, 2018), and Fusarium incarnatum FiPKS (Manoharan et al, 2019). However, fungal type III PKSs expressed in a fungal host yield compounds that are different from the recombinant proteins.…”
Section: Introductionsupporting
confidence: 62%
“…Type III PKSs catalyze the iterative condensation of a starter fatty acyl-CoA and of several extender units, mostly malonyl-CoA, as well as intramolecular lactone, aldol or Claisen cyclization (Lim et al, 2016;Shimizu et al, 2017). Although they can accept a wide range of fatty acyl-CoA starter units, from short to long linear (e.g., acetyl-CoA, steraoyl-CoA), branched (e.g., isobutyryl-CoA) or cyclic (e.g., p-coumaryl-CoA, benzoyl-CoA) molecules (Shimizu et al, 2017), they always show higher affinity for specific substrates (Funa et al, 2007;Rubin-Pitel et al, 2008;Li et al, 2011;Jeya et al, 2012;Ramakrishnan et al, 2018;Manoharan et al, 2019). The different affinity for diverse starter units is explained by changes in the structure of type III PKSs (Goyal et al, 2008;Rubin-Pitel et al, 2008;Seshime et al, 2010b;Mori et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The first group consists of 2'-oxoalkylresorcylic acid synthase (ORAS), BPKS, and AnPKS. [85][86][87] They use long straight-chain (> C 10 )a cyl-CoA starters with four malonyl-CoA extenders to produce resorcyclic acids( L-5-A), which are non-enzymatically decarboxylated to resorcinols. Some of these PKSs can use three or five extenders (L-4-A or L-6-A).…”
Section: Fungaltype III Pkssmentioning
confidence: 99%
“…In particular, incubation of peanut STS with p-fluorocinnamoyl-CoA (58), trans-3-furanacryloyl-CoA (59), or trans-3-(3-thienyl)acryloyl-CoA (60, Figure 16) in the presence of malonyl-CoA yielded stilbene-like products. The Botrytis cinerea type III PKS (BPKS) was also recently found to accept short-chain to long-chain acyl-CoAs (C2-C18) as starters with malonyl-CoA as the extender to generate triketide alkylpyrones ( Figure 15A) [87]. Tetraketide alkylpyrones were also formed from C10-C18 acyl-CoAs, while pentaketide alkylresorcylic acids 52 and pentaketide alkylresorcinols 53 were also produced from C16-C18 acyl-CoAs.…”
Section: Precursor-directed Biosynthesis Of Polyketidesmentioning
confidence: 99%